Mapping ASEAN Research Trends on Digital Parenting and Digital Literacy - Lukitowati, Suci; Paramita, Eka Putri; Triansyah, Andika (FKIP Universitas Lampung, 2025)
Mapping ASEAN Research Trends on Digital Parenting and Digital Literacy. Objectives: This study aims to map research trends on digital parenting and digital literacy in the ASEAN region during 2020–2024, identifying publication growth patterns, leading contributors, dominant themes, and existing research gaps. Methods: A bibliometric approach was employed to analyze documents retrieved from the Scopus database, focusing on publications addressing parental roles, digital literacy, and children's education. Data were processed using Biblioshiny and VOSviewer to examine publication types, author collaboration, geographic distribution, and keyword co-occurrence for thematic mapping. Findings: A total of 387 documents were analyzed based on annual growth, types of publications, author collaboration, geographical distribution, frequently occurring keywords, and the most highly cited articles. The findings indicate a significant increase in the number of publications, particularly in 2024. Indonesia emerged as the leading contributor, followed by Malaysia and Thailand. Keyword analysis revealed that terms such as digital literacy, students, e-learning, and media literacy dominated the literature. Keyword analysis showed an early dominance of digital literacy (344 occurrences), students (43), and e-learning (36), later shifting to media literacy (17), disinformation, and fake news, indicating a shift from technical online learning topics to important digital parenting issues. Despite the positive growth, international collaboration and systematic review publications remain limited. Conclusion: This study provides insights into the thematic evolution and identifies research gaps in the ASEAN region, highlighting the need for specific actions such as establishing ASEAN-wide research networks, developing culturally adapted parental digital literacy training, and promoting collaborative systematic reviews to strengthen evidence-based policies. These findings are expected to provide a foundation for creating a sustainable family digital literacy ecosystem in the digital transformation era.Keywords: digital parenting, digital literacy, media literacy, ASEAN.